Tratamento da persistência de canal arterial em recém-nascidos prematuros: análise clínica e cirúrgica - Locali, Rafael Fagionato [UNIFESP] (2008)
BACKGROUND: The surgical treatment of patency ductus arteriosus is indicated when the clinical intervention fails. However, this treatment may have some complications. OBJECTIVE: To analyze clinical and surgical aspects involved on the treatment of patency ductus arteriosus in premature newborn. METHODS: Twenty two premature newborns, submitted to surgical treatment for patency ductus arteriosus from January, 2000 to June, 2006, were evaluated. There were 77,3% female patients, the mean birth weight was 952,5g and the mean gestational age was 27 weeks. The use of vasoactive drugs, indometacin, echocardiograph parameters and complications, in the pre and postoperative periods were evaluated. RESULTS: In this casuistic 59,1% patients needed intratracheal intubation at birth, 77,3% needed surfactants, 59,1% used vasoactive drugs preoperative. The mean doses of indometacin were 3,43, with dose range 0,1 to 0,25 mg/Kg/day. The mean caliber of arterial duct patent was 1,96 mm. The surgical procedure was carried out through extrapleural approach in 59.1% of the patients, the mean time of postoperative intubation was 30,9 days, and 50% of the patients used vasoactive drugs postoperative. There were 18,1% postoperative complications (postoperative non-fatal complications). CONCLUSION: More than the half of the patients needed intratracheal intubation at birth, surfactant use and vasoactive drugs in the preoperative period. There was greater prevalence of the extrapleural approach during the surgery. In the postoperative period, there was less demand of vasoactive use and there was not deaths related to the surgical procedure.